Peran Badan Penanggulangan Bencana Daerah (BPBD) dalam Penanggulangan Bencana Banjir di Kelurahan Teluk Air, Kecamatan Karimun, Kabupaten Karimun - Nurisa Nazira Putri; Rudi Subiyakto; Novi Winarti (Social Issues Quarterly, 2023)
The minimal work program of the Regional Disaster Mitigation Agency (BPBD) has resulted in BPBD's efforts in the field not being maximized in anticipating flood disaster problems. This study aims to determine the role of BPBD and constraints in flood disaster management in Teluk Air Village, Karimun District, Karimun Regency. Data collected using instruments in the form of observation and documentation and developed by interviewing informants. The results of the study show that in Teluk Air Village, Karimun District, Karimun Regency there is preparedness in carrying out flood disaster management efforts from the Karimun Regency Regional Disaster Management Agency (BPBD) to deal with flood disasters. The local community also participates in flood prevention activities. The public is advised not to turn ditches or drains into garbage dumps. With limited human resources, the community is also asked to routinely clean ditches or waterways on a regular basis so that there is no blockage in the ditches which results in flooding. The existence of good conditions with related agencies or services as an effort to deal with flood disasters based on supportive conditions and in flood disaster management involves various parties.